Potential Unnecessity of Bismuth in Standard Triple Therapy for Clarithromycin-Susceptible Helicobacter pylori Infection - Seon Woo Oh; Keun Sol Min; Hyung Geun Kim; Sunmi Lee; Chul-Hyun Lim; Jung-Hwan Oh (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2025)
Objectives The standard first-line treatment for Helicobacter pylori infection typically involves proton pump inhibitors, amoxicillin, and clarithromycin (PAC), yet the eradication success rates are not entirely satisfactory. Recognizing bismuth’s antibacterial properties and its potential to enhance antibiotic efficacy, this study compared the eradication success rates of a 7-day course of PAC with bismuth (PACB) versus PAC alone in patients with clarithromycin-susceptible H. pylori infections. Methods We conducted a retrospective review at Eunpyeong St. Mary’s Hospital involving 499 patients with confirmed clarithromycin-susceptible H. pylori infection. These patients were treated either with PACB or PAC for 7 days. Clarithromycin resistance-associated point mutations were evaluated using reverse transcriptase polymerase chain reaction. Successful eradication was confirmed by a negative 13C-urea breath test. Results Of the patients, 261 received PACB therapy, and 238 received PAC therapy. The intention-to-treat analysis showed eradication success rates of 82.8% (216/261) for PACB and 89.1% (212/238) for PAC (p=0.093). The per-protocol analysis revealed eradication rates of 85.3% (215/252) for PACB and 90.5% (210/232) for PAC (p=0.081). The incidence of adverse effects was similar between the two groups, with 41.3% (104/252) in the PACB group and 34.1% (79/232) in the PAC group (p=0.102). Conclusions Adding bismuth to the standard 7-day PAC regimen did not significantly increase eradication rates in patients with clarithromycin-susceptible H. pylori infections compared to PAC alone.